Diagnosis Kesulitan Belajar Mahasiswa pada Mata Kuliah Statika dan Kekuatan Material - Sukaswanto Sukaswanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2013)
The objectives of this study were: (1) to analyse the causes underlying the students’ learning difficulties, (2) to identify the main learning difficulties encountered by the students, (3) to determine the most problematic topic in the course of Statics and Strength of Materials for the students (4) to assess the students’ efforts to overcome the learning difficulties. This study was ex-post facto with a descriptive-quantitative approach. The population comprised  140 students of the study program of Automotive Engineering, Faculty of Engineering, Yogyakarta Stae University. The samples were 35 students selected using purposive random sampling. The data was analysed using the descriptive technique in the form of percentages. The results showed in the course of  Statics and Strength of Materials: (1) the causes underlying the students learning difficulties was excessive sleepiness during the learning process, (2) the most widely encountered learning difficulty was poor understanding of the basic concepts, (3) the most problematic topic area is calculating torsion ( torque, torsional moment of detention, torsional stress, angle of twist) and (4) the students’ effort to overcome the learning difficulties was reviewing the Physics materials related to the subject.